PREFUL MRI for Monitoring Perfusion and Ventilation Changes after Elexacaftor-Tezacaftor-Ivacaftor Therapy for Cystic Fibrosis: A Feasibility Study - Martha Dohna; Andreas Voskrebenzev; Filip Klimeš; Till F. Kaireit; Julian Glandorf; Sophia T. Pallenberg; Felix C. Ringshausen; Gesine Hansen; Diane M. Renz; Frank Wacker; Anna‐Maria Dittrich; Jens Vogel‐Claussen (2024)
Purpose To assess the feasibility of monitoring the effects of elexacaftor-tezacaftor-ivacaftor (ETI) therapy on lung ventilation and perfusion in people with cystic fibrosis (CF), using phase-resolved functional lung (PREFUL) MRI. Materials and Methods This secondary analysis of a multicenter prospective study was carried out between August 2020 and March 2021 and included participants 12 years or older with CF who underwent PREFUL MRI, spirometry, sweat chloride test, and lung clearance index assessment before and 8–16 weeks after ETI therapy. For PREFUL-derived ventilation and perfusion parameter extraction, two-dimensional coronal dynamic gradient-echo MR images were evaluated with an automated quantitative pipeline. T1- and T2-weighted MR images and PREFUL perfusion maps were visually assessed for semiquantitative Eichinger scores. Wilcoxon signed rank test compared clinical parameters and PREFUL values before and after ETI therapy. Correlation of parameters was calculated as Spearman ρ correlation coefficient. Results Twenty-three participants (median age, 18 years [IQR: 14–24.5 years]; 13 female) were included. Quantitative PREFUL parameters, Eichinger score, and clinical parameters (lung clearance index = 21) showed significant improvement after ETI therapy. Ventilation defect percentage of regional ventilation decreased from 18% (IQR: 14%–25%) to 9% (IQR: 6%–17%) (P = .003) and perfusion defect percentage from 26% (IQR: 18%–36%) to 19% (IQR: 13%–24%) (P = .002). Areas of matching normal (healthy) ventilation and perfusion increased from 52% (IQR: 47%–68%) to 73% (IQR: 61%–83%). Visually assessed perfusion scores did not correlate with PREFUL perfusion (P = .11) nor with ventilation-perfusion match values (P = .38). Conclusion The study demonstrates the feasibility of PREFUL MRI for semiautomated quantitative assessment of perfusion and ventilation changes in response to ETI therapy in people with CF. Keywords: Pediatrics, MR–Functional Imaging, Pulmonary, Lung, Comparative Studies, Cystic Fibrosis, Elexacaftor-Tezacaftor-Ivacaftor Therapy, Fourier Decomposition, PREFUL, Free‐Breathing Proton MRI, Pulmonary MRI, Perfusion, Functional MRI, CFTR, Modulator Therapy, Kaftrio Clinical trial registration no. NCT04732910 Supplemental material is available for this article. © RSNA, 2024